Evaluating advance peace in Fresno, California: An interrupted times series analysis of a community-based gun violence intervention - Xing Gao; Juan R. Cabrera; David Padilla; Mahasin S. Mujahid; Jason Corburn (PLoS ONE, 2025)
Background Gun violence is a critical public health issue, contributing to the disproportionate burden of health inequities among racially and economically marginalized populations. Advance Peace, a community-driven gun reduction program that integrates street outreach workers to interrupt conflicts with trauma-informed programming to provide mentorship and support for young people at the center of urban gun violence, may be a strategy to reduce gun violence and build healthy communities. We assessed whether the implementation of Advance Peace in Fresno, California was associated with a reduction in gun-related violence, including homicides and assaults. We hypothesized that post-implementation of Advance Peace, there would be a reduction in both gun-related homicides and assaults. Methods Leveraging crime statistics from the Fresno Police Department on gun-related homicides and assaults between January 2014 and June 2023, we evaluated the impact of Advance Peace programming, implemented beginning in July 2021, on gun violence in Fresno. Descriptive analysis assessed average gun violence rates over time. We used interrupted time series models to assess the rates of gun violence associated with the implementation of Advance Peace in Fresno. Results In Fresno, there was evidence of a reduction in crime rates following the introduction of Advance Peace intervention. Two years post-intervention, there was a 46% decrease in the rate of all gun-related crimes, including both homicides and assaults (rate ratio: 0.54, 95% CI: 0.36–0.81). The intervention was also associated with a reduction in the rate of gun-related homicides (RR = 0.45, 95% CI: 0.21–0.95) and the rate of gun-related assaults (RR = 0.58, 95% CI: 0.38–0.89). Conclusion Findings from this study demonstrate that Advance Peace may be an effective strategy to reduce gun violence.